1921
DOI: 10.1084/jem.34.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of the Nasal Cavity and Postnasal Space to Chilling of the Body Surface

Abstract: Chilling of the body surface has been shown in earlier communications 1, ~ to cause reflex vasoconstriction and ischemia in the mucous membranes of the palate, palatine tonsils, and pharynx. The present study demonstrates a like reflex diminution in the blood supply of the nasal cavity and postnasal space (nasopharynx).In the postnasal space the reaction is closely similar to that previously described for the oropharynx; with chilling of the body surface the temperature of the nasopharyngeal mucosa has fallen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1930
1930
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…In our opinion sudden local drying, usually in the nasopharynx, is one of the most important factors in the onset of the common cold. A healthy nose suddenly comes under the influence of a vasomotor disturbance reflected from some remote point; the chilling of the body surface, 11 constipation, hunger or fatigue. After a very transient ischsemia, the turbinated bodies swell.…”
Section: Effects Of Local Dryingmentioning
confidence: 99%
“…In our opinion sudden local drying, usually in the nasopharynx, is one of the most important factors in the onset of the common cold. A healthy nose suddenly comes under the influence of a vasomotor disturbance reflected from some remote point; the chilling of the body surface, 11 constipation, hunger or fatigue. After a very transient ischsemia, the turbinated bodies swell.…”
Section: Effects Of Local Dryingmentioning
confidence: 99%
“…It is well established that chilling of the body surface will cause a pronounced vasoconstriction of blood vessels in the nose and upper airway. Mudd et al (65) reported that chilling of the body surface in human volunteers caused a pronounced ischaemia of the nasal mucosal surface that was measured as a fall in temperature via a nasal thermistor. In some subjects the depression of nasal mucosal temperature was more than 6 o C. Spiesman (66) demonstrated that cold stimuli such as cold air or ice filled cups, applied to the exposed areas of the body such as the back and feet, caused a pronounced decrease in the temperature of the nasal mucous membrane which was interpreted as being due to nasal vasoconstriction.…”
Section: Effects Of Acute Chilling the Body Surfacementioning
confidence: 99%
“…The nasal mucosa thickens and nasal airflow resistance increases on inhalation of irritant gases and many inflammatory mediators (Cole, 1982(Cole, , 1988, the mechanism probably being a combined vascular congestion with oedema and possibly some exudate. Inhaling cold air increases nasal airflow resistance (Cole, 1988) and reduces blood flow (Mudd, Goldman & Grant, 1921;Ralston & Kerr, 1945); the effect of warm air on airflow resistance is less certain. These results are consistent with a role of the capacitance system in airconditioning and filtration.…”
Section: Capacitance Vasculaturementioning
confidence: 99%